Psychotic‐like experiences associated with sleep disturbance and brain volumes in youth: Findings from the adolescent brain cognitive development study - Jessica R. Lunsford‐Avery; Katherine S. F. Damme; Teresa Vargas; Maggie M. Sweitzer; Vijay A. Mittal (Wiley, 2021)
Abstract Background Sleep disturbance is characteristic of schizophrenia and at‐risk populations, suggesting a possible etiological role in psychosis. Biological mechanisms underlying associations between sleep and psychosis vulnerability are unclear, although reduced sleep‐regulatory brain structure volumes are a proposed contributor. This study is the first to examine relationships between psychotic‐like experiences (PLEs; subclinical symptoms reflecting psychosis vulnerability/risk), sleep, and brain volumes in youth. Methods Brain volumes of five sleep‐related structures were examined in relation to PLEs and difficulties initiating and maintaining sleep (DIMS) in 9,260 9‐ to 11‐year‐olds participating in the Adolescent Brain Cognitive Development (ABCD) study. Analytic models examined relationships between DIMS, PLEs, and brain volumes, as well as DIMS as a mediator of brain volume-PLEs relationships. Although sleep regulation structures (i.e., thalamus, basal forebrain, and hypothalamus) were of primary interest, other potentially relevant structures to sleep‐related functioning and psychosis (i.e., hippocampus and amygdala) were also examined. Results PLEs were associated with increased DIMS as well as reduced volume in some, but not all, brain structures, including the thalamus and basal forebrain in children. DIMS was also associated with reduced left thalamus volume in youth. Increased DIMS partially, statistically mediated the relationship between left thalamic volume and PLEs, although the effect was relatively small. Conclusions Results highlight left thalamic volume as a potential neural mechanism underlying sleep disturbances and PLEs in childhood. Future studies should assess causal relationships between sleep, PLEs, and brain structure across adolescent development, interactions with other psychosis risk factors, and the role of sleep interventions in prevention of psychosis and a range of psychiatric conditions across the lifespan.